A randomized controlled trial of pegylated interferon-alpha with tenofovir disoproxil fumarate for hepatitis B e antigen-negative chronic hepatitis B: A 48-week follow-up study. Issue 12 (December 2020) - Bahardoust, Mansour; Mokhtare, Marjan; Barati, Mitra; Bagheri-Hosseinabadi, Zahra; Karimi Behnagh, Arman; Keyvani, Hossein; Agah, Shahram
Abstract: Background: Recent studies report incongruent finds regarding the addition of pegylated interferon -alpha (Peg- IFNα) to nucleos(t)ide analogues. This study was designed to compare the efficacy of Peg- IFNα and tenofovir disoproxil fumarate (TDF) combination therapy with each of the treatments separately. Methods: In this open-label, randomized clinical trial, treatment-naive hepatitis B e antigen (HBeAg)-negative patients were randomly assigned to three treatment groups: Group A: Peg- IFNα (180 mcg/week) with TDF (300 mg/day); Group B: TDF (300 mg/day); and Group C: Peg- IFNα (180 mcg/week). The intervention spanned 48 weeks and patients were followed up every 12 weeks. The primary end-point was HBV DNA load <20 IU/mL. Results: Groups A, B and C each comprised of 22, 23 and 22 patients, respectively. The number of patients with HBV DNA suppression in group A was significantly higher compared to groups B and C (P = 0.034). No significant difference was observed in the normalization trends of serum ALT levels between the three groups (P = 0.082). At week 48, combination therapy was significantly more effective in suppressing HBV DNA concentration to below the level of detection than TDF monotherapy (OR = 2.1, 95%CI: 1.18–4.15; P = 0.034). Furthermore, a comparison between monotherapy arms revealed that both interventions had similar effects on the overall outcome (OR = 1.24, 95%CI: 1.02–5.8; P = 0.062). Conclusion: A Peg- IFNα and TDF combination therapy resulted in improved virologic response and was safe in HBeAg negative patients. Monotherapy with Peg-IFNα or TDF procured limited benefits in comparison. Trial registration: This study was registered in the Iranian Registry of Clinical Trials (IRCT20181113041635N1) .